Program Impact Pathway Analysis Reveals Implementation Challenges that Limited the Incentive Value of Conditional Cash Transfers Aimed at Improving Maternal and Child Health Care Use in Mali. Issue 9 (25th July 2019) - Le Port, Agnes; Zongrone, Amanda; Savy, Mathilde; Fortin, Sonia; Kameli, Yves; Sessou, Eric; Diatta, Ampa Dogui; Koulidiati, Jean-Louis; Kodjo, Niamké Ezoua; Kamayera, Fainke; Mahamadou, Tanimoune; Martin-Prevel, Yves; et al.
ABSTRACT: Background: The program "Santé Nutritionnelle à Assise Communautaire à Kayes" (SNACK) in Mali aimed to improve child linear growth through a set of interventions targeted to mothers and children during pregnancy and up to the child's second birthday. Distributions of cash to mothers and/or lipid-based nutrient supplement to children 6–23 mo of age were added to SNACK to increase attendance at community health centers (CHCs). Objectives: The aim of this study, which was embedded in a cluster-randomized impact evaluation of the program, was to assess the incentive value of the cash in relation to CHC attendance. Methods: We used a mixed-methods approach. We collected quantitative data on cash receipt and CHC attendance in a midline survey of mother–child pairs ( n = 3443). A program impact pathway analysis guided qualitative data collection and analysis. Twelve CHCs were purposively selected in study groups that received cash. We conducted semistructured continuous observations of cash distributions in 11 CHCs ( n = 22) and semistructured qualitative interviews with frontline workers (FLWs) ( n = 71) and mothers ( n = 22) who were purposively selected from the midline survey. Results: FLWs' knowledge of the objective and implementation plan of the cash program component was limited. A challenging physical environment and insufficient cash available for each distribution were identified as causes of irregularities in cash distributions. Most mothers mentioned having to return several times to receive their cash. Child health was identified as the main motivation to attend CHCs and cash was described as an additional benefit. Conclusion: Implementation constraints related to remoteness and inaccessibility may have undermined the incentive value of the cash transfers in the SNACK program. Additional research is needed to identify interventions that not only incentivize mothers to participate but that can be implemented effectively and with high quality in challenging contexts such as rural areas of Mali.